The Development Of Learning Tools Using Contextual Teaching Learning Model For Improves Solving Capability Student Problems On Application Materials Differential And Integral - Silitonga, Rustani; Siagian, Pargaulan; Sitompul, Pardomuan (FKIP Universitas Muhammadiyah Tangerang, 2024)
This research is development research so that the product of this research is a learning tool with the Contextual Teaching Learning model on differential and integral application material. The aim of this research is to describe: 1) the validity, practicality and effectiveness of learning tools using the contextual teaching learning model to increase students' problem solving abilities in differential and integral application material; 2) increasing students' problem solving abilities using learning tools with contextual teaching learning models on the developed differential and integral application material. This research uses the ADDIE development model which consists of 5 development stages, namely Analyze, Define, Development, Implementation and Evaluation. The results of this research were obtained: 1) the learning device using the contextual teaching learning model to increase students' problem solving abilities in the differential and integral application material developed has met the valid criteria according to experts and from the results of trial I and trial II of the learning device has met the practical and effective criteria; 2) Increasing problem solving abilities using learning tools with a contextual teaching learning model on differential and integral application material that has been developed seen from the N-gain value in trial I of 0.41, increasing to 0.42 in trial II, and is within